UPAYA PBB DALAM PENYELESAIAN SENGKETA KASHMIR (INDIA-PAKISTAN): STUDI PENDEKATAN KAJIAN ISLAM KONTEMPORER - Diinu Tsabitul Azmi; Mukhsin Achmad (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
Abstrack The Kashmir conflict between India and Pakistan has been a chronic source of regional instability since the mid-20th century, despite various mediation and resolution efforts initiated by the United Nations (UN). This study critically evaluates the effectiveness of UN interventions in resolving the Kashmir dispute, highlighting the geopolitical constraints and internal resistance that limit the implementation of resolutions. Originally, this research expands the analytical framework by integrating the perspective of contemporary Islamic studies as both a theoretical and practical lens. We argue that Islamic principles founded on justice, peace, consultation (syura), and reconciliation offer a conflict resolution paradigm that has not been extensively explored in the Kashmir context. Initial findings suggest that while the UN faces structural challenges, integrating an Islamic approach one that emphasizes consensus building and substantive justice can provide novelty and essential depth in formulating sustainable solutions. This represents a significant contribution to the literature on international conflict resolution, particularly concerning disputes rooted in historical and cultural complexities. Keywords: Kashmir, India-Pakistan, UN, Contemporary Islam